Direito agrário: aspectos reais e obrigacionais - Pardo Filho, Milton (2006)
These essay results of a researching process accomplished in the Social Law area. The objective was to join and systematize the required and real aspects of the Agrarian Law. The methodology adopted had strong influence from the bibliographic research combined with the analyses of the agrarian situation in Brazil, indicating to the following results: A) The Agrarian Law is a activity of the civil law; B) The Agrarian Law centralize the property, with important real reflexes: Rural Real Estate, Rural Module, Small Landed Estate, Family Property, Small Property, Medium Property, Large Landed Estate, Indigenous Lands, Colonization, Squatter, Federally-owned Lands, Zone Border, Dismembering and Housing Subdivision; C) It is not possible an Agrarian Law complete understanding without the least knowing such institutes; D) The Agrarian Law suffers likewise strong contractual influence: Rural Real Estate Purchasing and Sale, Rural Leasing and Rural Partnership; E) The Agribusiness, as a group of business related to the land exploration, very important the Agrarian Law, by its social and economical importance. In the end, it is concluded that the Agrarian Law should be incorporated definitely as one of the activities most important of the Brazilian Civil Law, by the fact that all the agrarian questions guide good part of our wealth production and the job generation, being of the utmost importance its required and real effects from there current